ANALISIS PENGARUH NON PERFORMING LOAN, PROPORSI INVESTASI, LOAN TO DEPOSIT RATIO, RASIO KEWAJIBAN TERHADAP EKUITAS DAN BANK SIZE TERHADAP SHAREHOLDER VALUE PADA BANK KONVENSIONAL YANG LISTING DI BEI TAHUN 2011 HINGGA 2014 - Alusia, Yesy Hartina; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2015)
This research aims to analyze the influence of the Non Performing Loan, Investment Proportion, Loan to Deposit Ratio, Liability to Equity Ratio, and Bank Size to Shareholder Value of conventional bank which are listing in Indonesia Stock Exchange during 2011 until 2014 and measured by Market to Book Value (MBV). The population that included in this research consisted of all banking companies which are listing in Indonesia Stock Exchange during 2011Â until 2014. So the number of total population is 36 banks. After passed the step of purposive sampling method it was gotten 31 banks over 4 years, so there were 124 data. The data analysis method used is multiple linier regression analysis with the classical assumption test. The results of this research showed that Investment Proportion and Loan to Deposit Ratio have negative and significant effect to Shareholder Value (MBV), Bank size has a positive and significant effect to Shareholder Value, meanwhile Non Performing Loan and Liability to Equity Ratio have no significant effect to Shareholder Value.